Analysis of deixis and optimistic values in Kun Anta song lyrics - Amelya, Asy Syifa Reza; Dienana, Arina; Anjaswara, Bening; Al Farisi, Mohamad Zaka; Solihah, Isna Fitria (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2024)
A popular language expression is music, as it is a symbolic avenue for conveying thoughts and emotions. In this research, Kun Anta songs will be analyzed and classi-fied into several types of deixis using Levinson’s framework, while correlating the con-tained optimism with relevant phenomena. It is shown that deixis is fundamental in expression. This study adopts a qualitative descriptive approach, focusing on the pro-cess and providing descriptive data to better understand the phenomenon under investigation. The data undergoes three phases of analysis: data reduction, display, and conclusion drawing, followed by verification. In our analysis we have found that the song Kun Anta reveals 53 persona deixis, 1 place deixis, 5 discourse deixis, 0 time deixis, and 0 social deixis, suggesting the dominance of persona deixis. The song's lyrics urge lis-teners to embrace authenticity and believe in their capabilities. Kun Anta’s lyrics closely correlate with the insecurity phenomenon, offering a significant moral contribution as a response.